Sistem Informasi Pelayanan Administrasi Desa Genting Berbasis Web: Sistem Informasi Pelayanan Administrasi Desa Genting Berbasis Web - Heru Aji Pangestu Heru; Kirman; Sri Handayani (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2022)
Abstract— The correspondence service process at the genting village office still uses the conventional method. The process of servicing and recording correspondence is done manually where the data of the letters that have been made are still recorded in a book, so they are vulnerable to damage and scattered when stored for a long period of time. In searching for the data of letters that have been made, difficulties often occur because the data is very large and often lost. The purpose of this research is to create a village website which can later be used by the village government as a village information medium, so that rural communities in particular and the general public can access information about genting villages. In this research, the system development method uses the Incremental Model, the system design uses context diagrams, data flow diagrams (DFD), and Entity Relationship Diagrams (ERD) and the system testing method uses blackbox testing. The test results of the Web-Based Genting Village Administration Service Information System based on the test results of the website-based village administration service system as expected based on 3 variables, namely, the assessment of the display variable including the